The Challenges of Implementing Smart City Management in Iran’s Public Transport Sector - sepideh moradi; abdollah motevali gale kalayi; hamed nezami asl sisi; mohammad hosein seifosadat (Iranian Journal of Information Processing & Management)
Transportation and development of intra-city roads are the fundamental factors of urban development. Access and communication are the basis of urban dynamics and any mutual growth, especially economic growth in an urban area. Therefore, the transportation sector plays a fundamental role in both the emergence and continuation of any development and progress in cities. On the other hand, any development action in the field of public transportation as an important part of transportation management will directly affect the growth and quality of urban life. Smart management as one of the solutions to improve the quality of life of Iranian citizens as a technology-based and experienced solution can be the solution to many problems of urban life in Iran. The main issue of the research refers to the fact that despite the existence of infrastructure such as the Internet, smart traffic cameras, the presence of experts with up-to-date knowledge in the field of ITS (intelligent transportation system), motivated specialized forces in creating successful startups in the field of public transportation, and even the comprehensive emphasis of executive officials on the priority of developing public transportation facilities, why are we not witnessing the implementation of smart management in the field of public transportation in Iran? Therefore, it is expected that there are definitely challenges, and the aim of this research is to identify the challenges of implementing smart city management in the field of public transportation in Iran. This research is of a research-applied type and was selected using the Delphi method and a specialized panel of 50 people using non-probability sampling and a combination of purposeful or judgmental and chain methods. The members of this panel are transportation experts and experts and managers of public transportation organizations. After analyzing the surveys using the Delphi method and using SPSS software, the identified challenges were classified into six basic categories, including: 1- The challenge of the lack of strategic plans and strategies in the field of public transportation, 2- The challenge of economic isolation, 3- The challenge of securing financial resources, 4- The challenge of cultural and managerial knowledge, 5- The challenge of the lack of supportive laws, 6- Security challenges, as challenges for implementing smart city management in the field of public transportation.